Specific absorption rates in the human head and shoulder for passive UHF RFID systems. (26th February 2009) - Arumugam, D.; Engels, D.
In this paper, we use a human head and shoulder model to extend the analysis of SAR in the human head due to radiation caused by UHF RFID readers. We use an FEM human head and shoulder model with a voxel size of 8 mm for the tetrahedral and 25 distinct tissues to analyse the peak one-voxel SAR, spatial-peak 1 g cube of tissue SAR, spatial-peak 10 g cube of tissue SAR and the average SAR in the human head. We study the SAR in the human head at 1 W radiated power of a 7.4 dB RFID reader patch antenna at distances of 10 cm, 100 cm and 1, 000 cm from the human head. We show that an RFID reader at 10 cm from the human head presents a SAR above 1.6 W/kg for both the spatial-peak 1 g and 10 g cube of tissue, the maximum value allowed by the FCC in the USA.